ChemInform Abstract: Simple Modular Synthetic Approaches to Asymmetric NN′N′′, NN′C, or NN′P‐Type Amido Pincer Ligands: Synthesis, Characterization, and Preliminary Ligation Studies. Issue 47 (3rd November 2016) - Herasymchuk, Khrystyna; Huynh, Jennifer; Lough, Alan J.; Roces Fernandez, Laura; Gossage, Robert A.
Abstract: A palladium complex of a newly prepared NN′N′′‐pincer ligand proves as an active catalyst for the allylation of benzaldehydes by allyltributylstannane.